Impact evaluation of EU funds: Examples in infrastructure projects - Spiridonovs, Jurijs (Business: Theory and Practice, 2011)
Being one of investment areas within EU Cohesion policy the sector of public infrastructure frequently faces the issue of efficiency. This issue largely arises from the lack of theoretical and practical concepts on how the evaluation techniques could achieve rigorous estimations of the investment impact on the current processes in the sector. The present paper seeks to contribute to these discussions by defining crucial problems in developing rigorous estimations relevant to public infrastructure projects and setting the assumptions. The research method is comparative and logical analysis of the theoretical concepts, methods and conclusions, published in scientific literature including policy analysis.